Neurocircuitry of attention in methamphetamine induced psychosis: a comparison against schizophrenia patients and healthy controls - Hsieh, Jennifer Hsin-Wen (Department of Psychiatry and Mental Health, 2022)
Background Methamphetamine induced psychosis (MAP) and schizophrenia present with similar positive symptoms of psychosis, are characterized by evidence of attentional impairment, and show symptomatic response to treatment with dopamine antagonists. At the same time, MAP is considered a transient condition, while schizophrenia can be conceptualized as a neurodevelopmental disorder. Despite advances in the neurobiology of these two conditions, the extent to which their underlying attentional neurocircuitry show overlaps or differences has not often been directly compared. This thesis compared MAP, schizophrenia and healthy controls, in order to examine overlap and differences in 1) subcortical regulation of cortical inhibition and excitability, 2) resting state cortical and subcortical connectivity, and the dynamics of rhythmic neural activity between states, and 3) cortical-cortical connectivity using event related potential (ERP) responses to stimuli with a continuous performance task (CPT). Methods Outpatients treated for MAP and schizophrenia were recruited through hospitals and psychiatric institutions in the Western Cape. A final cohort of 24 MAP and 28 schizophrenia and 32 healthy control participants were included in the analyses for this thesis. For the cortical silent period (CSP) paradigm, the participant was asked to maintain isometric contraction between the thumb and index finger while TMS pulses at 120% and 140% resting motor threshold (RMT) were delivered to the primary motor cortical area corresponding to the abductor pollicis brevis (APB). Parameters extracted from CSP data included the latency to motor evoked potential (MEP), MEP amplitude and CSP duration. Electroencephalographs (EEGs) were performed with bilateral prefrontal, frontal, frontal temporal, central and parietal electrode locations. Relative EEG frequency power data were extracted from 3 stages during the EEG session, including states of eyes open, eyes closed, and during performance of the CPT. The CPT consisted of a series of random consonant letters. Participants were asked to respond to the letter "S" with a finger press only if it was the 3rd consecutive occurrence. ERP data were extracted and averaged from consecutive cues (S1 and S2), target (S3) and distractor (individual "S") stimuli in the CPT task. ERP data were analysed for group differences in N100, P200, N200 and P300 amplitudes and latencies at each electrode location with sufficient signal quality. Results In the CSP protocol, MAP and schizophrenia groups showed smaller MEP amplitudes at both 120% and 140% RMT stimulation levels in comparison to controls. Both MAP and schizophrenia groups had lower alpha and higher delta relative frequency band power, with schizophrenia showing significant differences from controls at more electrode positions than MAP. While controls demonstrated a decrease in alpha power between the eyes closed and eyes open resting states, this did not occur in MAP or schizophrenia. During the CPT, both MAP and schizophrenia achieved fewer correct targets and showed slower reaction times than healthy controls. In addition, MAP responded more often than the other two groups to the S2 stimulus (which required response inhixii Abstract bition). ERP analysis found smaller N100, larger P200, larger N200 and larger P300 amplitudes in MAP in response to stimuli requiring inhibition than in schizophrenia and controls, whereas schizophrenia showed longer P300 latencies in response to the target and distractor stimuli than in MAP and controls. Conclusions MEP results suggest that MAP and schizophrenia may have similar subcortical dysregulation, suggestive of altered dopaminergic regulation in the basal ganglia-thalamus-cortex loop. EEG frequency power results suggest that MAP and schizophrenia both display an inflexibility of subcortical systems involved in adaptation to environmental changes, suggesting deficiencies in the CT-TRN-TC loop in both MAP and schizophrenia. CPT performance and the pattern of ERP alterations in MAP suggests greater cholinergic impairment during attentional performance in MAP than in schizophrenia. Taken together, while there is considerable overlap in cortical-subcortical inhibition and connectivity in MAP and schizophrenia, there are also important differences; findings that emphasize both the similarities and dissimilarities that are seen clinically.